THE MANAGEMENT OF A PORTFOLIO IN THE CONDITIONS OF ECONOMIC CRISIS - ILIE RĂSCOLEAN; CLAUDIA ISAC; ROBERT SZABO (Annals of the University of Petrosani: Economics)
The need for money is one of the main financial goals of any company. Such needs have led to specific segments of demand and supply that demand for money and the money supply, in particular capital. Were created following specific markets: financial markets, with specialized division of labour in money markets and capital markets. Capital market is to supply and demand for medium and long term capital, with the same role as the financial market in general, having featured the long duration of maturity. From the viewpoint of the agents involved two types of markets that is the primary market, which are negotiated in the presence of primary and secondary securities issuer, that and his participation, and market secondary market investors, financial flows are directed to a investor to another. Institution typical secondary capital market is the stock market. Coverage of financial instruments, according to EU directives in force, is broad, including both tradable capital market instruments and money market instruments. Investment is defined in national accounts as gross fixed capital formation is the value of durable goods purchased by the production units to be used at least one year in production processes. The investment flow is therefore measured over a period, often a year, noted that the yield from an investment is proportional to the risk assumed. Investing in shares of the opportunity to diversify revenue and achieving consistent earnings, earnings from sales and purchases of shares may be significantly higher earnings from a bank.